Book Design Of Bilingual Illustration Story History Of The Struggle "Sultan Ageng Tirtayasa" From Banten (International Journal of Psychosocial Rehabilitation, 2020)
History is an event that happened in the past which is arranged based on the relics of various events. These relics are called historical sources. history will be understood by the next generation of the previous society as a mirror to progress in the life of society, nation and state. By knowing history we can have an attitude of patriotism which is an attitude of respecting the services of heroes, loving the motherland, and loving culture. As regions in Indonesia are rich in historical stories, Banten is a province on the island of Java, Indonesia which holds a myriad of history. The history of the heroism of Sultan Ageng Tirtayasa who was a hero who was known to be determined to fight against the Dutch invaders. Sultan Ageng Tirtayasa's struggle against the Dutch in Serang, Banten made him awarded the title of National Hero by the Indonesian government. But the story is not widely known by the young generation themselves themselves at this time. The lack of knowledge about the heroic sultan ageng tirtayasa story, the authors designed a story book about the hero of the sultan ageng tirtayasa presented with illustrations as a support to facilitate the contents of the story to be conveyed. In this case illustration becomes an important role as a visual media that is able to attract the interest of readers, especially the younger generation so that it can cause a sense of nationalism and love the region again.